2012
DOI: 10.1128/aac.00720-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of TMC207 and Its N -Desmethyl Metabolite in a Murine Model of Tuberculosis

Abstract: TMC207 is a first-in-class diarylquinoline with a new mode of action against mycobacteria targeting the ATP synthase. It is metabolized to an active derivative, N-desmethyl TMC207, and both compounds are eliminated with long terminal halflives (50 to 60 h in mice) reflecting slow release from tissues such as lung and spleen. In vitro, TMC207 is 5-fold more potent against Mycobacterium tuberculosis than N-desmethyl TMC207, and the effects of the two compounds are additive. The pharmacokinetic and pharmacodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 20 publications
(27 reference statements)
10
105
1
1
Order By: Relevance
“…Bedaquiline drug concentrations at the end of treatment were higher than the values previously reported at week 8 (13). M2 values were low, as expected (3). No drug-drug interactions were expected as no CYP3A4 inhibitors were coadministered.…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…Bedaquiline drug concentrations at the end of treatment were higher than the values previously reported at week 8 (13). M2 values were low, as expected (3). No drug-drug interactions were expected as no CYP3A4 inhibitors were coadministered.…”
Section: Resultscontrasting
confidence: 42%
“…Since the antimicrobial action of bedaquiline is exposure dependent (2,3), it is necessary, as with any drug with exposuredependent killing characteristics, that target exposures are reached. Current data from animal studies on optimal drug exposure have not yet been translated to and validated in human studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedaquiline similarly accumulates to very high levels in the tissues in both people (30) and mice (31), and the accumulated drug in tissue homogenates results in carryover and growth inhibition of M. tuberculosis on non-charcoal-containing agar (23). Despite the extremely high tissue concentrations, bedaquiline is maintained at a relatively low and steady concentration in serum, which is thought to be due to steady release of the drug from the tissues (30); and it has also been suggested that it is the serum drug levels, rather than the tissue drug levels, that represent active drug (31).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the effect of antibiotic interactions in macrophages and in mice, the antibiotic activity of the combination treatment was defined as the log 10 CFU reduction as previously reported with slight modifications (32,40). Briefly, the antimycobacterial activity was assessed by counting the CFU from the macrophage lysates or the homogenates of inoculated organs on 7H10 agar supplemented with 10% OADC and determining the log 10 CFU per ml after 5 days.…”
Section: Clinical Isolate Sources Growth Conditions and Inoculum Prmentioning
confidence: 99%